MODEL BIMBINGAN NABI MUHAMMAD SAW DALAM MELAKUKAN KADERISASI PEMIMPIN - Maturidi Maturidi; Arifin Zain (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: The Prophet Muhammad was a successful religious leader as well as a state leader. In addition to being able to make himself successful in leading the religion and state, he is also successful in conducting leader regeneration. The success of the leader regeneration carried out by the Prophet Muhammad. It can be seen from the many successful leaders after him such as Abu Bakr, Umar bin Khattab, Usman bin Affan, Ali bin Abi Talib who all became khulafaur rashidin, and Ma'awiyah bin Abi Sufyan who was the founder of Umayyah. In conducting the research, the writer uses library research method, using qualitative method with a historical approach. The results show that in carrying out the regeneration of the leader of the Prophet Muhammad. using a model of guidance including modeling, lectures, assignments, question and answer method and so on. Keywords: Guidance, Prophet Muhammad, regeneration, leader